Adaptive dynamic sliding mode control for space manipulator with external disturbance. Issue 4 (2nd October 2019) - Zhao, Jing; Jiang, Sen; Xie, Fei; Wang, Xian; Li, Zeyun
ABSTRACT: In this paper, a novel adaptive dynamic sliding mode control(ADSMC) methodology is developed for space manipulator control systems with external disturbance. The proposed ADSMC approach can make the systems stable and accurately track the desired signals in the presence of external disturbances. Firstly, the simplified dynamic model of the manipulator is introduced. Then, the proposed adaptive dynamic sliding mode(ADSM) controller is given, which is proved to be able to guarantee high tracking accuracy via effectively estimating the disturbance boundary. Finally, experimental results show that the dynamic sliding mode controller proposed in this paper can not only track the desired trajectory, but also present strong robustness for external disturbance, meanwhile effectively reduce the chattering phenomenon generated by switching between different sliding mode surfaces.